Intentional, bold leadership for a modern, gender-balanced hydrospatial workforce - Stewart, Helen F.; Mihailov, Maria Emanuela; Obura, Victoria; Plackal Njanaseelan, Geetha; Sharma, Shereen (The International Hydrographic Review, 2025)
This Note joins the conversation of the IHO Empowering Women in Hydrography and Women in the Hydrospatial domain (Hains et al., 2022) in a broader sense, elevating key points and commonalities with the goal of contributing value by taking the position that the pursuit of Gender Balance is a Leadership issue – not a “Women” issue – that must be addressed to succeed as a 21st Century organization. Successful gender-balanced efforts are underway in the global Hydrospatial community, and these models can be leveraged as a communal map for progress in this realm. Lastly, this note offers a simple synthesis of expert perspectives on necessary leadership steps and strategies for achieving business or professional goals with a gender-balanced team.